Radiation from Fast and Slow Traveling Waves - Sutinjo, Adrian; Okoniewski, M.; Johnston, R. (Institute of Electrical and Electronics Engineers, 2008)
This article presents an overview of the radiation from fast and slow traveling waves. The goal is to describe the mechanisms that give rise to the radiation in a leaky-wave antenna (LWA). An infinite aperture distribution and line-source assumptions will be used to convey the concepts. In addition, the relationship between the leaky-wave antenna and other types of traveling wave antennas will be elucidated.